Evaluation of TRAF6 in a large multiancestral lupus cohort - Namjou, Bahram; Choi, Chan-Bum; Harley, Isaac T. W.; Alarcón-Riquelme, Marta E.; Kelly, Jennifer A.; Glenn, Stuart B.; Ojwang, Joshua O.; Adler, Adam; Kim, Kwangwoo; Gallant, Caroline J.; Boackle, Susan A.; Criswell, Lindsey A.; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2012)
Objective Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease with significant immune system aberrations resulting from complex heritable genetics as well as environmental factors. We undertook to study the role of TRAF6 as a candidate gene for SLE, since it plays a major role in several signaling pathways that are important for immunity and organ development. Methods Fifteen single‐nucleotide polymorphisms (SNPs) across TRAF6 were evaluated in 7,490 SLE patients and 6,780 control subjects from different ancestries. Population‐based case–control association analyses and meta‐analyses were performed. P values, false discovery rate q values, and odds ratios (ORs) with 95% confidence intervals (95% CIs) were calculated. Results Evidence of associations was detected in multiple SNPs. The best overall P values were obtained for SNPs rs5030437 and rs4755453 (P = 7.85 × 10−5 and P = 4.73 × 10−5, respectively) without significant heterogeneity among populations (P = 0.67 and P = 0.50, respectively, in Q statistic). In addition, SNP rs540386, which was previously reported to be associated with rheumatoid arthritis (RA), was found to be in linkage disequilibrium with these 2 SNPs (r2 = 0.95) and demonstrated evidence of association with SLE in the same direction (meta‐analysis P = 9.15 × 10−4, OR 0.89 [95% CI 0.83–0.95]). The presence of thrombocytopenia improved the overall results in different populations (meta‐analysis P = 1.99 × 10−6, OR 0.57 [95% CI 0.45–0.72], for rs5030470). Finally, evidence of family‐based association in 34 African American pedigrees with the presence of thrombocytopenia was detected in 1 available SNP (rs5030437) with a Z score magnitude of 2.28 (P = 0.02) under a dominant model. Conclusion Our data indicate the presence of association of TRAF6 with SLE, consistent with the previous report of association with RA. These data provide further support for the involvement of TRAF6 in the pathogenesis of autoimmunity.